Institusionalisasi Pembiasaan Keagamaan di Masjid Urban: Analisis Konstruksi Sosial Peter L. Berger - Ananda Nur Husain Al-Hafifi; Muhamad Ridwan Effendi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the process of religious habituation among congregants at Masjid Jami’ Al-Barokah Yasda, South Jakarta, through the perspective of Peter L. Berger’s theory of social construction. The mosque implements a series of religious programs conducted consistently on a daily basis, including ta’lim, recitation of Rotibul Haddad, congregational shalat tasbih, Yasin Tahlil Barzanji, silaturahmi, and jaulah. This research aims to understand how these programs are designed, implemented, and interpreted so as to shape the religious patterns of the congregation. This study employs a qualitative descriptive approach, with data collected through in-depth interviews with the head of the Mosque Management Board (DKM) and direct observation of religious activities. The findings indicate that religious habituation in this mosque is formed through an interconnected process of social construction: religious programs are formulated by mosque administrators as an expression of religious values and vision (externalization), subsequently carried out on a regular basis until they are accepted as traditions and a collective identity of the mosque (objectivation), and ultimately internalized by congregants as values that shape religious attitudes and consciousness of piety (internalization) in their daily lives.Overall, these religious activities are oriented toward sustaining Rahmatan lil ‘Alamin da‘wah da‘wah that promotes goodness, inner peace, and social benefit for both congregants and the surrounding community. The findings demonstrate that religious habituation, when managed consistently and adaptively, is capable of fostering a living religious culture, strengthening piety, and generating tangible social impacts within an urban religious context.